THE ART OF VISUAL EFFECTS: A COMPARATIVE REVIEW OF KOLLYWOOD AND HOLLYWOOD CINEMA - J, Manojkumar; .D, Rajkamal; J, Evans Dennison; . Mothe, Prashant S (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2025)
The advancement of visual effects (VFX) has significantly transformed cinematic storytelling in both Kollywood and Hollywood. Each industry has uniquely adapted emerging technologies to enrich narratives, enhance audience engagement, and reflect their respective cultural identities. This study explores the similarities and differences in VFX application, audience reception, and production approaches in these two prominent film industries. Through a comparative analysis of key case studies, this research examines how landmark films in Kollywood and Hollywood utilize VFX to drive visual storytelling, influence box office performance, and project cultural values. By highlighting the evolution of VFX technologies and their integration into cinematic practices, the study aims to understand their current role and predict their future impact on global filmmaking. Special attention is given not only to technological advancements but also to the cultural context that shapes their visual expression. This analysis offers valuable insights for filmmakers aiming to craft compelling narratives that resonate with diverse audiences in an increasingly globalized film industry